1974
DOI: 10.1002/oms.1210090808
|View full text |Cite
|
Sign up to set email alerts
|

o‐nitroaniline derivatives. IV—The mass spectra of o‐nitroanils

Abstract: Abstract-The principal feature of the mass spectra of o-nitroanils, ArCH=NC,H,NO,(o-), is an intense peak corresponding to the [ArCO]+ ion; this implies oxygen transfer from the nitro group to the azomethine carbon during the fragmentation process. In this series of anils, loss of OH from the molecular ion is not apparently an important fragmentation pathway, in contrast to the fragmentation of o-nitrobenzylideneanilines. Benzylideneaniline derivatives with an o-nitro substituent in both rings have mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In the case of tautomer b, the transfer of an oxygen atom to a neighbouring double bond has to take place, in a manner similar to that observed for other kinds of compounds containing a double bond ortho to the nitro group. [28][29][30] This can lead to the loss of a formyl radical, again as reported for compounds in which a double bond is ortho to the nitro group. 29,30 The loss of a ketene molecule (H 2 C=C=O) most likely proceeds via a McLafferty rearrangement.…”
Section: Compoundmentioning
confidence: 67%
“…In the case of tautomer b, the transfer of an oxygen atom to a neighbouring double bond has to take place, in a manner similar to that observed for other kinds of compounds containing a double bond ortho to the nitro group. [28][29][30] This can lead to the loss of a formyl radical, again as reported for compounds in which a double bond is ortho to the nitro group. 29,30 The loss of a ketene molecule (H 2 C=C=O) most likely proceeds via a McLafferty rearrangement.…”
Section: Compoundmentioning
confidence: 67%
“…In a previous paper, 5 we have shown that, although other simple anils of the general formula 1 also undergo primary fragmentation of the type illustrated, this 'normal' fragmentation process may be suppressed, in some cases almost entirely, by other competing ortho interactions. In the mass spectrum of N-o-nitrobenzylidene-0-nitroaniline (2j it is the nitro group in the amine-derived ring which interacts preferentially with the CH=N group, by transferring oxygen to the benzylidene carbon: this leads to the formation of an o-nitrobenzoyl ion (Scheme 2, pathway A).…”
mentioning
confidence: 80%